FUNCTIONAL RECOVERY ENHANCEMENT BY TIGER MILK MUSHROOM, LIGNOSUS RHINOCEROTIS IN A SCIATIC NERVE CRUSH INJURY MODEL AND MORPHOLOGICAL STUDY OF ITS NEUROTOXICITY - M. Farha; L. Parkianathan; N.A.I. Abdul Amir; V. Sabaratnam; K.-H. Wong (Journal of Animal and Plant Sciences, 2019)
Insights into the process of peripheral nerve regeneration are essential for the development of novel therapies. We tested the activity of aqueous extract from Lignosus rhinocerotis mushroom on nerve regeneration in a rat model of sciatic nerve crush injury and to examine (if any) toxicity effect of the extract on nervous tissues. Activities of aqueous extracts were compared to mecobalamin, a drug for peripheral neuropathies. 24 adult rats were randomly divided to 4 groups, the negative controls, positive controls, low and high dosages of aqueous extracts. Functional recovery was evaluated by sensitivity to thermal pain and toe-spreading reflex. Morphological changes in the nervous tissues was assessed by haematoxylin and eosin stain. Hot plate test showed acceleration of sensory recovery in low dosage group compared to other groups. Return of toe-spreading in the crushed limb was accomplished by day 12 and day 16 in low and high dosage groups, respectively after crush injury. Microscopic examination showed normal features of Peripheral and Central Nervous Tissues. There were no abnormal clinical signs detected. Oral administration of low dosage of L. rhinocerotis aqueous extract is capable to enhance motor and sensory functional recovery after nerve injury and had no adverse effects on nervous tissues.
Keywords: Lignosus rhinocerotis; aqueous extract; peripheral nerve regeneration; functional recovery; neurotoxicity